PIJAT OKSITOSIN PADA IBU NIFAS UNTUK PENINGKATAN PRODUKSI ASI DI PMB NAZRIWATI, S.Tr.Keb - Selawati, Selawati; Lestari Nurul Aulia, Devy (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2024)
The puerperium is an important period, as the risk of maternal and infant morbidity and mortality increases during this period. Hemorrhage is the leading cause of maternal death worldwide and most occur before 24 hours postpartum. Therefore, the birth attendant must ensure that the uterus contracts properly, so that bleeding does not occur. The postpartum period is influenced by many factors, one of which is socio-cultural. Indonesia is a country consisting of various tribes and cultures that have their own health traditions. Not all existing traditions have a bad effect on health but there are also some that have a positive impact on health. Efforts to assist and therapy to shape the coping skills of postpartum women are with complementary therapy. Complementary therapy is a therapy that is used as a companion in conventional therapeutic efforts that a person has done. This type of research is descriptive by applying a case study approach. The implementation of this research was carried out at the PMB Nazriwati, S.Tr.Keb on Mrs. W by providing complementary health education education for mothers in the postpartum period